The HLA-II immunopeptidome of SARS-CoV-2 - Weingarten-Gabbay, Shira; Chen, Da-Yuan; Sarkizova, Siranush; Taylor, Hannah B.; Gentili, Matteo; Hernandez, Gabrielle M.; Pearlman, Leah R.; Bauer, Matthew R.; Rice, Charles M.; Clauser, Karl R.; Hacohen, Nir; Carr, Steven A.; et al. (Cell reports (Cambridge), 2024)
Targeted synthetic vaccines have the potential to transform our response to viral outbreaks, yet the design of these vaccines requires a comprehensive knowledge of viral immunogens. Here, we report severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) peptides that are naturally processed and loaded onto human leukocyte antigen-II (HLA-II) complexes in infected cells. We identify over 500 unique viral peptides from canonical proteins as well as from overlapping internal open reading frames. Most HLA-II peptides colocalize with known CD4+ T cell epitopes in coronavirus disease 2019 patients, including 2 reported immunodominant regions in the SARS-CoV-2 membrane protein. Overall, our analyses show that HLA-I and HLA-II pathways target distinct viral proteins, with the structural proteins accounting for most of the HLA-II peptidome and nonstructural and noncanonical proteins accounting for the majority of the HLA-I peptidome. These findings highlight the need for a vaccine design that incorporates multiple viral elements harboring CD4+ and CD8+ T cell epitopes to maximize vaccine effectiveness. [Display omitted] •Immunopeptidome analysis of SARS-CoV-2 peptides naturally presented on HLA class II•Some HLA-II peptides originate from noncanonical SARS-CoV-2 proteins ORF9b and ORF3c•Class I and class II HLA complexes present different subsets of viral proteins Weingarten-Gabbay et al. map the repertoire of SARS-CoV-2 peptides naturally presented on HLA-II. The authors uncover HLA-II peptides originating from noncanonical ORFs and highlight striking differences between viral proteins that are presented on class I and class II HLAs, resulting in distinct targets for killer and helper T cells.